2015
DOI: 10.1073/pnas.1507719112
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale serum protein biomarker discovery in Duchenne muscular dystrophy

Abstract: SignificanceDuchenne muscular dystrophy (DMD) is a rare and devastating muscle disease caused by mutations in the X-linked DMD gene (which encodes the dystrophin protein). Serum biomarkers hold significant potential as objective phenotypic measures of DMD disease state, as well as potential measures of pharmacological effects of and response to therapeutic interventions. Here we describe a proteomics approach to determine serum levels of 1,125 proteins in 93 DMD patients and 45 controls. The study identified 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
235
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(259 citation statements)
references
References 44 publications
16
235
0
Order By: Relevance
“…RELT/ TNFRSF19 was previously described as significantly decreased in DMD patient 56 highlighting importance of this group of cytokine receptors primarily involved in pleatoric activities as inflammation, apoptosis, proliferation, survival and differentiation. Another intriguing protein that emerged from our study is the neural immunoglobulin family adhesion molecule Contactin-1, significantly reduced in abundance in mdx sera.…”
Section: Discussionmentioning
confidence: 92%
“…RELT/ TNFRSF19 was previously described as significantly decreased in DMD patient 56 highlighting importance of this group of cytokine receptors primarily involved in pleatoric activities as inflammation, apoptosis, proliferation, survival and differentiation. Another intriguing protein that emerged from our study is the neural immunoglobulin family adhesion molecule Contactin-1, significantly reduced in abundance in mdx sera.…”
Section: Discussionmentioning
confidence: 92%
“…mice performed using Somalogics SomaMERs 151 , in combination with Western blotting using a monoclonal antibody from abcam, which, at the time, was reported to be specific for GDF11. Subsequent reports from our group 104 and others 87, 143, 152 revealed that the SomaMER and mAb used in these initial studies cross-react with MSTN, and so, while these studies are consistent with a reduction in the circulating pool of GDF11 and MSTN in aged animals, these data cannot discriminate the relative impact of aging on systemic levels of GDF11 specifically. A report from Egerman and colleagues argued that circulating levels of GDF11 might actually increase with age, based on the results of Western blot, RNA expression, and GDF11-specific immunoassay 87 .…”
Section: Current Controversiesmentioning
confidence: 86%
“…Another study demonstrated that WFIKKN2 is more expressed in a chicken line that has been selected for 60 years for rapid growth of the skeletal muscle tissue (Ross 708 broiler bird) than in a legacy chicken line (Illinois bird) [46]. The concentration of WFIKKN1 in the serum also decreased with age in a Duchenne muscular dystrophy patient while it increased with age in controls [47]. Further, WFIKKN2 is one of the 32 most highly enriched proteins in human embryonic stem cells-conditioned medium [48] known to enhance the proliferation of mouse and human muscle progenitors.…”
Section: Wfikkn Expression In Musculoskeletal Systemmentioning
confidence: 99%